Sectoral Shocks and Spillovers : An Application to COVID-19 - Das, Sonali (IMF Working Papers; Working Paper ;, 2021)
This paper examines the role of sectoral spillovers in propagating sectoral shocks in the broader economy, both in the past and during the COVID-19 pandemic. In particular, we study how shocks that occur within a sector itself and spillovers from shocks to other sectors affect sectoral activity, for a large sample of countries from 1995 to 2014. We find that both supply and demand shocks-measured as changes in, respectively, productivity and government purchases at the sector level-have large spillover effects on sector-level gross value added and on a sector's share of the economy. We then use these historical estimates, together with the network structure of global production, to quantify the spillovers from the economic shock associated with the pandemic. We find spillover effects to be sizeable, making up a significant fraction of the overall decline in activity in 2020.Our results have implications for the design of policies with a sectoral dimension.